2003
DOI: 10.1002/jobm.200390011
|View full text |Cite
|
Sign up to set email alerts
|

Transformations of testosterone and related steroids in Absidia glauca culture

Abstract: In the following study, the course of transformations of testosterone and its derivatives with an additional C(1)-C(2) double bond and/or 17alpha-methyl group or without 19-methyl group in Absidia glauca culture was investigated. The fungi were observed to hydroxylate these compounds and to oxidise the 17beta-hydroxyl group. The products of 6beta, 7alpha, 7beta, 11alpha, 12beta or 15beta hydroxylation were obtained. 19-Nortestosterone was also hydroxylated at the 10beta position.The position and stereochemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…Reduction of a ketone to hydroxyl group was also confirmed by 1 H NMR, with the appearance of an additional downfield triplet at d 3.66 (J 0/8.5 Hz) and it also had one singlet at d 4.54. On the basis of published data (Huszciza & Dmochowska-Gladysz 2003a), the narrow profile of signals at d 4.53 and 0.05 Á0.1 ppm downfield shift for H-4 confirmed the presence of 6b-hydroxyl group in compound VI. The IR spectrum of VII showed peaks for hydroxyl, carbonyl on cyclopentane and a carbonyl group conjugated with a double bond at 3449, 1735, 1658 cm (1 , respectively.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…Reduction of a ketone to hydroxyl group was also confirmed by 1 H NMR, with the appearance of an additional downfield triplet at d 3.66 (J 0/8.5 Hz) and it also had one singlet at d 4.54. On the basis of published data (Huszciza & Dmochowska-Gladysz 2003a), the narrow profile of signals at d 4.53 and 0.05 Á0.1 ppm downfield shift for H-4 confirmed the presence of 6b-hydroxyl group in compound VI. The IR spectrum of VII showed peaks for hydroxyl, carbonyl on cyclopentane and a carbonyl group conjugated with a double bond at 3449, 1735, 1658 cm (1 , respectively.…”
Section: Resultssupporting
confidence: 66%
“…An 1 H NMR spectrum of VII showed an additional signal at d 3.34 Á3.59 as a triplet split into a doublet, characteristic of a 7a-proton. The appearance of a carbon resonance at d 75.2 in the 13 C NMR spectra of VII confirmed the position of the hydroxyl group at 7b (Huszciza & Dmochowska-Gladysz 2003a;Owen et al 1988). …”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…There are some reports on hydroxylation of methyltestosterone at the C-6E [18], C-7D [16], C-7E [19], C-9D [20], C-11D [21], C-12E [21], and C-15D [17] positions as well as the production of 6E,11D- [18] and 6E,12E-dihydroxy compounds [21]. In this study, it was demonstrated that a 5-day incubation of M. racemosus in the presence of methyltestosterone under appropriate conditions results in the formation of metabolites 2 to 4.…”
Section: -4mentioning
confidence: 99%
“…However, this does not seem to be the case for other positions available for hydroxylation on the D ring, as indicated by the isolation of compounds 3 and 4 from the cultures of M. racemosus in the present study. For most other fungi, hydroxylation on the D ring does not appear to be directly influenced by the presence of a 17-methyl group [21,24].…”
Section: -4mentioning
confidence: 99%